Some Basic Aspects of Militia Activities in Ukrainian SSR in 1933 (Law and Safety, 2019)
The authors’ objective was to study the main aspects of militia’s activities in 1933. This objective is specified in the following tasks: to highlight the work of militia regarding the introduction of passportization in Ukraine; to reveal certain aspects of its activity during the grain supplies in 1933. The authors of the article highlight for the first time the role of militia in carrying out grain supplies in 1933 in Ukraine. Materials on the implementation of passportization in the Republic have been supplemented through the prism of the tasks and activities of militia in this direction.It has been noted that the system of registration and control of population in the cities of Ukrainian SSR was radically changed at the end of 1932. The exact time for the introduction of passportization was chosen not by chance – collectivization in Ukraine ended and the Holodomor began. The result of these processes was a massive flight of peasants from villages who tried to survive and escape from the Holodomor. The main feature of the new passport system was the fact that passports were issued only to those residents of cities, workers’ settlements, state-owned enterprises and new buildings who reached the age of 16 years. An absolute majority of villagers did not have the opportunity to get this document and therefore became attached to their places of residence.Practical conduction of passportization of the population in Ukrainian SSR revealed an unfavorable demographic situation in the country and the presence of a large number of declassed persons who did not have a permanent job or committed crimes. The introduction of the passport system positively affected the organization of combating crime and ensuring state security, the registration of receptees was established. At the same time, passportization was accompanied by numerous repressions of judicial and extrajudicial nature. Militia being a part of the State Political Administration took an active part in the grain supplies campaign of 1932-1933, which led to the Holodomor. That activity had negative and repressive nature. Officers of militia also investigated the cases involving cannibalism.
Keywords: Ukraine; 1933; NKVS; militia; passport system; Holodomor